Guide to Trollope. - Gerould, Winifred Gregory, 1885-1955 (Princeton University Press, 2014)
Trollope fans and all who want to increase their knowledge of that great Victorian novelist will welcome this guide to the worlds he created. In alphabetical entries on the multitude of characters and places in his novels the reader can quickly find the material to follow the career of a favorite--Lady Glencora, perhaps, or Mr. Harding. Frequent use of quotation lends the authentic Trollope touch. A summary of the plot of each novel is included, as are Trollope's own estimates of his works. Maps of the geography of the novels are a delightful feature of the guide.